PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN PRESTASI BELAJAR SEJARAH - Nurhayati, Esti; Haikal, Husain; Joebagio, Hermaanu (Sebelas Maret University (UNS), 2016)
Background: This study was conducted in order to determine whether the use of inquiry method can improve learning competence in the subjects of history at SMA Negeri 1 Tract class XI IPS 4 the 2nd half of 2012/2013, the number of respondents as many as 35 students.Methods: The study was a classroom action research. Source of data in the form of documentation, observation or observation and tests. The data source is taken test results. Techniques used in the data collection in the form of technical documentation, observation, and test the tools used in the collection of data such as documents of value, items pre test and post test first cycle, second cycle and third cycle. The research was conducted in three cycles with activities covering action planning, action, observation and reflection. This class action research uses the content validation.Results: The design or the design of teaching history refers to the curriculum SBC applicable, historical material which has been applied to the content standards, basic competence, teaching materials that have been neat. Learning the inquiry method can improve the competence of learning history. The improvement can be seen from the number of students who scored at or above the KKM is 100% and the average of the values are increased by 96%, from an average 43.07 into 80.57.